Fluktuasi Tinggi Muka Air Tanah Gambut Di Lahan Perkebunan Kelapa Sawit Desa Kubu Kecamatan Kubu Kabupaten Kubu Raya - Rossie Wiedya Nusantara; Gusti Zakaria Anshari; Wahyu Ramadhan (Jurnal Ilmu Lingkungan, 2023)
The Government of Indonesia requires oil palm plantations on peatlands to regulate the ground water table at -40 cm all year. Factors that determine the groundwater are rainfall, tidal conditions, land conversions and drainage conditions. This research aims to measure the ground water table and water balance of the oil palm plantation on the drained peats. The research was conducted from August – October 2021. The grounwater table were measured with peizoemeter installed in three blocks at an interval of 250 m, 500 m, and 750 m. The measurements were at 8 am dan 4 pm. The groundwater table ranges -4 cm to -39 cm. It seems that rainfall and tides do not have influence heights of the groundwater table in this oil palm. Further research must be done to investigate this phenomenon. A comprehensive monitoring of groundwater table covering both rainy and dry seasons is required to record the differences of groundwater tables.